Evaluation of the Understanding of Grade IV Students of State Elementary School (SDN) 07 Ampenan, Mataram City in Presenting Pancasila Values - Nining Hardianti; Santi Farm (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2025)
This study aims to evaluate the understanding and implementation of Pancasila values by grade IV students of SDN 07 Ampenan, Mataram City. Using a qualitative descriptive approach, this study involved 23 students as subjects. Data were collected through comprehension tests, observations, interviews, and documentation. The results showed that the level of students' understanding of Pancasila varied, with 26% of students in the category of very good, 61% good, and 13% adequate. The aspect of understanding the basic concept of Pancasila has the highest percentage (45%), while the application of Pancasila values in daily life is the lowest (22%). Character observation shows that students in the very good category have a high attitude of discipline, responsibility, and tolerance. Internal factors such as learning motivation, and external factors such as teacher and family support affect outcomes. This study concludes that although most students understand the values of Pancasila, the improvement of interactive-based learning methods and direct practice is needed to support applicative understanding.